Biomass exploitation - a challenge finding its way to reality - Singhvi, Mamata S.; Gokhale, Digambar V. (Current Science, 2015)
Lignocellulosic biomass holds the key to supplying the basic needs of society for sustainable production of chemicals and fuels without impacting the human food supply. The production of second-generation biofuels and chemicals from lignocellulosic biomass has not yet been commercialized due to its complex and recalcitrance structure. Therefore, the challenges involved in the production of lignocellulosic biomass-derived fuels and chemicals must be addressed. Search for economic pretreatment methods has been recognized as one of the main hurdles for processing of biomass to biofuels and chemicals. The conversion of all biomass components, lignin in particular, would greatly contribute to the economic viability of biomass-based processes for second-generation biofuels and chemicals. Hydrolysis of lignocellulose carbohydrates into fermentable sugars requires a suitable cellulase enzyme cocktail acting on both raw as well as pretreated biomass. Depending on raw material and pretreatment technology, the enzyme mixtures must be designed to degrade biomass carbohydrates. Recent publications on GVL-pretreatment to solubilize and degrade carbohydrates in biomass and CelA enzyme acting on raw biomass would probably meet the challenges in biomass conversion technologies.